Sensing, communications and monitoring for the smart grid - Duan, Dongliang, author; Yang, Liuqing, advisor; Scharf, Louis L., committee member; Luo, Jie, committee member; Song, Rui, committee member (Colorado State University. Libraries, 2012)
With the increasing concern for environmental factors, reliability, and quality of service, power grids in many countries are undergoing revolution towards a more distributed and flexible "smart grid." In the development of the envisioned smart grid, situational awareness takes a fundamental role for a number of crucial advanced operations, such as power flow scheduling, dynamic pricing, energy management, wide area control, wide area protection etc. To fulfill the mission of situational awareness across various entities in the grid, more advanced sensing, communications and monitoring techniques need to be introduced to the existing power grid. In this research, we will first address the issue of battery power efficiency (BPE) in a wireless sensor network (WSN) which is essential for the sensing system lifetime. We show that the BPE can be improved either by selecting a more battery-power-efficient modulation format or by developing a cooperative communications scheme. Then, to transmit the sensed data over the scarse wireless bandwidth, we adopt cognitive radio as a possible solution. To enable the cognitive radio communication, we aim at improving both the reliability and efficiency of the overall system via cooperative spectrum sensing. With these fundamental communication capabilities available for the sensed data, we then investigate wide area power grid monitoring based on synchronized measurements from newly developed devices such as phasor measurement units (PMUs), mode meters and so on. In addition, an optimal fusion technique is studied as a good foundation for detection in wireless sensor networks, with application to event detection in the power grid.
Keywords: wireless communications; smart grid; wireless sensor network; cognitive radio; power efficiency